Electronic Handout on the History of the Gondang Winangun Sugar Factory Since the Malaise Crisis of 1930-1982 to Enhance Knowledge of Colonialism - Dharu Sinar Mustikasari; Ganda Febri Kurniawan (Indonesian Journal of History Education, 2024)
This research aims to develop electronic teaching materials in the form of handouts regarding the dynamics of the Gondang Winangun Sugar Factory since the Malaise crisis for students of SMA N 2 Klaten (a high school). This development focuses on two main challenges: first, although students are enthusiastic about interactive history learning, teachers need more engaging and easy-to-understand teaching materials; Second, although students are interested in local history, local historical resources are often limited and difficult to access. This teaching material is presented digitally as an interactive website accessed through various electronic devices. The research method uses Research and Development (R&D) with the ADDIE model, including the stages of analysis, design, development, implementation, and evaluation. Data was obtained through observations, interviews, and questionnaires from validators, history teachers, and students. The assessment results showed that this teaching material obtained an average assessment percentage of 82.3% from media experts, 90.2% from material experts, 91.1% from history teachers, and 88% from students. With these results, electronic handouts are considered feasible and effective as alternative teaching materials at SMA N 2 Klaten, especially for class XI.